Linking Social Protection and Humanitarian Assistance in the Philippines - Aldaba, Fernando T (Archīum Ateneo, 2019)
This study is part of a multi-country collection of cases showing that humanitarian assistance and social protection programmes are not necessarily mutually exclusive. As will be shown in the next section, there is an increasing amount of literature discussing the integration of humanitarian assistance into social protection systems or the linkage of disaster risk responses with specific social safety net programmes. The nexus maybe seen through synergies via common frameworks, platforms and systems utilized in such programmes. The Philippines, a developing economy in Southeast Asia continues to tackle the problems of poverty and vulnerability among its 100 million population. It lies in the “Pacific Ring of Fire” and is visited regularly by typhoons, ravaged by flooding, and occasionally hit by destructive earthquakes. It also has two long running conflicts with rebel groups that have displaced thousands of its citizens in hot areas. Despite being a middle income country and owing to the recurrent nature of crises, the country has a permanent presence of humanitarian actors (UN agencies, international, and national NGOs) ready to complement government efforts during emergencies. This specific case study will showcase the linking of humanitarian assistance and social protection in two instances where cash transfer for relief and recovery by two humanitarian agencies, the World Food Programme (WFP) and United Nations Children’s Fund (UNICEF) successfully “piggybacked” on the Pantawid Pamilya Pilipino Program (4Ps), a lead social protection programme of the Department of Social Welfare and Development (DSWD) during the aftermath of typhoon Haiyan.